Relationship of serum testosterone, sperm production, and testis traits with fertility of Mangalarga Marchador stallions - Rua, Miguel Alejandro S.; Quirino, Celia R.; Bartholazzi Junior, Aylton; Vega, Wilder Hernando O.; Barreto, Marcus Antônio P.; Bastos, Rosemary (Revista Colombiana de Ciencias Pecuarias, 2018)
Background: Assessing breeding soundness is important to predict the potential fertility of stallions. Objective: To investigate the association of testis traits, total number of spermatozoa, and testosterone with fertility of Mangalarga Marchador breed stallions. Methods: The traits measured were testicular length, width and height, right and left testicular volume and total testicular volume. We also evaluated the total number of spermatozoa (TNS), serum testosterone concentration and fertility of stallions (by embryo recovery from donor mares) in the breeding and non-breeding seasons during 1 year. Analysis of variance was performed to verify the effects of age category (AC; young/adult) and reproductive season on the traits. Correlations and repeatability of the traits were also calculated. Results: The AC did not influence testis traits (p > 0.05). Reproduction season affected left testicular length, left testicular height, right testicular width and height (p < 0.05). The AC and season affected testis volume (p < 0.05). There were no effects of AC and season on TNS and testosterone (p > 0.05). We observed strong correlations between all testicular measurements and testicular volume (0.53 to 0.75), medium correlation between TNS and testis volume (0.32), and low correlation between testosterone and testis traits (0.20). Repeatability of the characteristics of left and right testis was medium to high (0.22 to 0.78). Embryo recovery rate was 60% and its correlation with TNS was 0.44. Conclusion: Testis size evaluation is recommended over the evaluation of serum testosterone concentration to predict sperm output. Sperm output (TNS) is a good predictor of stallion fertility.